2008
DOI: 10.1111/j.1462-5822.2008.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid raft-dependent uptake, signalling and intracellular fate ofPorphyromonas gingivalisin mouse macrophages

Abstract: SummaryLipid rafts are cholesterol-enriched microdomains involved in cellular trafficking and implicated as portals for certain pathogens. We sought to determine whether the oral pathogen Porphyromonas gingivalis enters macrophages via lipid rafts, and if so, to examine the impact of raft entry on its intracellular fate. Using J774A.1 mouse macrophages, we found that P. gingivalis colocalizes with lipid rafts in a cholesterol-dependent way. Depletion of cellular cholesterol using methyl-b-cyclodextrin resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 67 publications
(109 reference statements)
4
52
0
2
Order By: Relevance
“…However, these inhibitors only minimally affected the binding of the membrane-coated beads and bacteria. Cholesterol depletion by M␤CD suppressed the ability of P. gingivalis for intracellular persistence and cytokine induction in mouse macrophages (33) and abolished actin polymerization induced by P. gingivalis OM vesicles (32). Lipid raft-dependent internalization was also observed with Treponema denticola Mspdeduced peptide conjugate, P34BSA, which induced actin stress fiber formation through PI3K and RhoA activation, although lipid raft activation by P34BSA, but not lipid raft-dependent internalization, is linked to PI3K and RhoA activation (34).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, these inhibitors only minimally affected the binding of the membrane-coated beads and bacteria. Cholesterol depletion by M␤CD suppressed the ability of P. gingivalis for intracellular persistence and cytokine induction in mouse macrophages (33) and abolished actin polymerization induced by P. gingivalis OM vesicles (32). Lipid raft-dependent internalization was also observed with Treponema denticola Mspdeduced peptide conjugate, P34BSA, which induced actin stress fiber formation through PI3K and RhoA activation, although lipid raft activation by P34BSA, but not lipid raft-dependent internalization, is linked to PI3K and RhoA activation (34).…”
Section: Discussionmentioning
confidence: 87%
“…For lipid raft inhibition, we used a concentration for each inhibitor that did not show discernable cytotoxicity in the cells. Lipid raft-dependent internalization of Porphyromonas gingivalis, a representative periodontopathogen, has been also demonstrated in epithelial cells and macrophages (32,33). Lipid raft inhibitors, in particular M␤CD, drastically reduced the internalization of beads coated with the OM vesicles of P. gingivalis in HeLa cells and of P. gingivalis whole bacteria in mouse macrophages.…”
Section: Discussionmentioning
confidence: 92%
“…P. gingivalis has been shown to induce lipid raft-dependent phagocytosis in macrophages [5]. To invade host cells that are not professional phagocytes, pathogens utilize diverse molecules and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis, a gram-negative anaerobe, is a major colonizer of gingival tissues and has been etiologically implicated in various forms of periodontitis [1]. Cellular invasion by P. gingivalis has been proposed as a possible virulence factor, affording protection from the host immune responses and contributing to tissue damage [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that bacteria utilize lipid rafts or raft-associated molecules for adhesion to or invasion of host cells (11,29,34,59). With H. pylori, previous studies have shown that cholesterol-rich microdomains are required for VacA binding, delivery, and intoxication of cells (20,28,41,48).…”
Section: Discussionmentioning
confidence: 99%